Oskarżyć i potępić. Przebieg rozprawy przeciw Zygmuntowi Augustyńskiemu (i innym) z 1947 r. jako przykład procesu politycznego z okresu początków stalinizmu w Polsce - Pleskot, Patryk (Komunizm: System - Ludzie - Dokumentacja, 2023)
The article focuses on the course of the trial of Zygmunt Augustyński, editor-inchief of People’s Newspaper [“Gazeta Ludowa”], convicted in August 1947 (along with two other defendants) and sentenced to 15 years in prison. The reconstruction of the subsequent stages of the trial serves to analyse the political direction of this show trial whose primary goal was to attack the Polish People’s Party’s milieu. The ideological staging of the trial was specific; since it took place in the pre-Stalinist period, the staging was not as successful as in the later years. Still, this court case can serve as an example of the communist lawlessness.